High‐Pressure Geophysical Properties of Fcc Phase FeHX. (29th January 2018) - Thompson, E. C.; Davis, A. H.; Bi, W.; Zhao, J.; Alp, E. E.; Zhang, D.; Greenberg, E.; Prakapenka, V. B.; Campbell, A. J.
Abstract: Face centered cubic ( fcc ) FeHX was synthesized at pressures of 18–68 GPa and temperatures exceeding 1, 500 K. Thermally quenched samples were evaluated using synchrotron X‐ray diffraction (XRD) and nuclear resonant inelastic X‐ray scattering (NRIXS) to determine sample composition and sound velocities to 82 GPa. To aid in the interpretation of nonideal (X ≠ 1) stoichiometries, two equations of state for fcc FeHX were developed, combining an empirical equation of state for iron with two distinct synthetic compression curves for interstitial hydrogen. Matching the density deficit of the Earth's core using these equations of state requires 0.8–1.1 wt % hydrogen at the core‐mantle boundary and 0.2–0.3 wt % hydrogen at the interface of the inner and outer cores. Furthermore, a comparison of Preliminary Reference Earth Model (PREM) to a Birch's law extrapolation of our experimental results suggests that an iron alloy containing ∼0.8–1.3 wt % hydrogen could reproduce both the density and compressional velocity ( VP ) of the Earth's outer core. Key Points: X‐ray diffraction and nuclear resonant inelastic X‐ray scattering were performed on fcc FeHX to determine densities and sound velocities to 82 GPa The Earth's outer core may contain up to 0.8–1.3 wt % hydrogen based on matching the density and velocities of variable stoichiometry iron hydrides to PREM The hydrogen content of Earth's core is highly dependent on the influence of temperature on the Birch's law relationship in iron alloys